Mechanical Behavior Evolution and Damage Characterization of Coal under Different Cyclic Engineering Loading - Huajun Wang; Jian Li (Geofluids)
The cyclic loading causes the strength change of porous rocks, which can be frequently encountered in underground coal mining. In order to quantify the cumulative damage of porous coal, multilevel uniaxial cyclic compressive tests were carried out considering different loading frequencies. The results show that under cyclic loading, Young’s modulus of coal shows a first drastic increase and then decrease trend in terms of the number of loading-unloading cycles, while the Poisson’s ratio gradually increased at lower peak stress amplitudes and then increased sharply with peak cyclic stress amplitude until losing load bearing capacity, following a stepwise rising trend. At a higher loading frequency, volumetric compressibility-dilatancy transition is shifted to an earlier time. The loading/unloading response ratio (LURR) was used to evaluate the damage of coal under cyclic loading. It is found that LURR is an effective parameter to evaluate the damage of coaly rock under cyclic loading and is also useful in distinguishing different deformation mechanism at different loading stages. The results also show that the damage of coal can initiate at the early stage of cyclic loading at a low loading frequency; however, the increase in frequency of cyclic loading can delay the damage time, requiring a relatively higher level of peak cyclic stress amplitude.